GAMBARAN PERILAKU KELUARGA SADAR GIZI PADA KELUARGA YANG MEMILIKI ANAK USIA 0-59 BULAN DI WILAYAH KERJA PUSKESMAS OESAPA - Yumita Elisabet Bella; Herliana Monika Azi Djogo; Angela M. Gatum (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2022)
Nutrition conscious family (KADARZI) is a family that is able to recognize, prevent and overcome nutritional problems of each member. The assessment of the nutritional status of the family is based on five main indicators, namely weighing regularly, providing exclusive breastfeeding for the first 6 month, consuming a variety of foods, using iodized salt and consuming vitamin A nutritional supplements as recommended. Research Purpose was Describe the behavior of nutritionally conscious families in children aged 0-59 month in the working area of the Oesapa Public Health Center. This type of research is descriptive analytic with a cross sectional approach. The sampling technique used in this research is purposive sampling. The sample in this study amounted to 55 people who were obtained using a purposive sampling technique in accordance with the specified inclusion criteria. Result Showed that the behavior of weighing 90,9% was good, exclusive breastfeeding behavior was good 94,5%, the behavior of consuming various foods was not good 70,9%, the behavior of using iodized salt was not good 54,4% and the behavior of consuming nutritional supplements (Vitamins A) good 92,7%. Conclusion most of the behavior of the family aware of good nutrition. The result of this study are expected that health workers can improve the provision of education about the importance of Kadarzi behavior in children aged 0-59 months. Keywords: Kadarzi behavior, toddlers 0-59 months